2021
DOI: 10.1155/2021/6678297
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Size and Sintering Temperature on the Formation of Mullite from Kyanite and Aluminum Mixtures

Abstract: The effect of particle size and sintering temperature of the mixtures of kyanite and metallic aluminum related to the thermal transformation of kyanite into primary mullite and free silica was studied. In addition, the reaction between α-Al2O3 (in situ produced by aluminum oxidation) and the silica was obtained in cristobalite structure from kyanite to obtain secondary mullite. The kyanite powders were milled by 0.5, 3, 6, and 12 hours and then were mixed with aluminum powder, which were previously milled by 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In kaolin‐added porous SiC, the mechanical strength of the sample increased due to the formation of cristobalite and mullite, which are the transformation products of kaolin 15,41 . Kaolin starts to change into mullite above 1000°C, 20 and this transformation intensifies with increasing temperature (1100–1600°C) 15,42 . Das et al 41 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In kaolin‐added porous SiC, the mechanical strength of the sample increased due to the formation of cristobalite and mullite, which are the transformation products of kaolin 15,41 . Kaolin starts to change into mullite above 1000°C, 20 and this transformation intensifies with increasing temperature (1100–1600°C) 15,42 . Das et al 41 .…”
Section: Resultsmentioning
confidence: 99%
“…15,41 Kaolin starts to change into mullite above 1000 • C, 20 and this transformation intensifies with increasing temperature (1100-1600 • C). 15,42 Das et al 41 also reported an enhanced amount of mullite formation by increasing the kaolin content in the samples. The XRD results of the present study clearly indicate the formation of mullite and cristobalite at 1300 • C, whereas no such phase was detected at 1100 • C. This finding reveals that a temperature of 1100 • C was insufficient for the formation of cristobalite and mullite, which was also obvious from the mechanical strength results (Figure 14A).…”
Section: Flexural Strengthmentioning
confidence: 91%
“…Size reduction in the feedstock is very effective in reducing the firing temperature for powder synthesis, and reducing the powder size increases the surface activity and the number of nucleation sites, shortening the diffusion distance and improving the degree of homogeneity. 11 Hernández et al 12 studied the effect of kyanite powder particle size and sintering temperature on the synthesis of mullite. The results show that the transformation and growth rate of mullite depend on the particle size and specific surface area, and the reduction of particle size affects the thermal decomposition of kyanite, thus causing expansion as well as secondary mullite formation reactions and increasing shrinkage, while grinding significantly increases the reactivity of kyanite.…”
Section: Introductionmentioning
confidence: 99%
“…Size reduction in the feedstock is very effective in reducing the firing temperature for powder synthesis, and reducing the powder size increases the surface activity and the number of nucleation sites, shortening the diffusion distance and improving the degree of homogeneity 11 . Hernández et al 12 . studied the effect of kyanite powder particle size and sintering temperature on the synthesis of mullite.…”
Section: Introductionmentioning
confidence: 99%